Self-Reported Antihypertensive Medication Class and Temporal Relationship to Treatment Guidelines. Issue 2 (February 2022) - Egan, Brent M.; Yang, Jianing; Rakotz, Michael K.; Sutherland, Susan E.; Jamerson, Kenneth A.; Wright, Jackson T.; Ferdinand, Keith C.; Wozniak, Gregory D.
Abstract : The greater antihypertensive responses to initial therapy with calcium channel blockers (CCBs) or thiazide-type diuretics than renin-angiotensin system blockers as initial therapy in non-Hispanic Black (NHB) adults was recognized in the US High BP guidelines from 1988 to 2003. The 2014 Report from Panel Members Appointed to the Eighth Joint National Committee (2014 aJNC8 Report) and the 2017 American College of Cardiology/American Heart Association High Blood Pressure Guideline were the first to recommend CCBs or thiazide-type diuretics rather than renin-angiotensin system blockers as initial therapy in NHB. We assessed the temporal relationship of these recommendations on self-reported CCB or thiazide-type diuretics monotherapy by NHB and NHW adults with hypertension absent compelling indications for β-blockers or renin-angiotensin system blockers in National Health and Nutrition Examination Surveys 2015 to 2018 versus 2007 to 2012 (after versus before 2014 aJNC8 Report). CCB or thiazide-type diuretics monotherapy was unchanged in NHW adults (17.1% versus 18.1%, P =0.711) and insignificantly higher after 2014 among NHB adults (43.7% versus 38.2%, P =0.204), although CCB monotherapy increased (29.5% versus 21.0%, P =0.021) and renin-angiotensin system blocker monotherapy fell (44.5% versus 31.0%, P =0.008). Although evidence-based CCB monotherapy increased among NHB adults in 2015 to 2018, hypertension control declined as untreated hypertension and monotherapy increased. While a gap between recommended and actual monotherapy persists, evidence-based monotherapy appears insufficient to improve hypertension control in NHB adults, especially given evidence for worsening therapeutic inertia. Initiating treatment with single-pill combinations and timely therapeutic intensification when required to control hypertension are evidence-based, race-neutral options for improving hypertension control among NHB adults. Abstract : Supplemental Digital Content is available in the text.